Right heart tamponade and intermittent cyanosis due to Morgagni diaphragmatic hernia in a neonate - Umesh Dyamenahalli; Paula Williams; Thomas K. Lee (Elsevier, 2020)
Congenital Morgagni hernia (CMH) is a rare congenital anomaly is typically diagnosed in childhood and on occasions in adults during work up of unexplained respiratory infections or gastrointestinal symptoms. The average age of laparoscopic repair of CMH was 3.3 years. We describe a newborn with fetal aberrant ductus venosus with progressive right ventricular dilation prompting early delivery. Post-natally, the baby had frequent episodes of cyanosis. Echocardiogram during distress showed compression of the inferior vena cava and of the right heart, with significant right to left shunt through patent foramen ovale. Infant underwent successful laparoscopic diaphragmatic hernia repair with resolution in her episodes of cyanosis. Keywords: Morgagni diaphragmatic hernia, Neonate, Cyanosis, Tamponade